2017
DOI: 10.1007/s10865-017-9845-z
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of standardized methods to specify behavioral pediatric obesity prevention interventions

Abstract: Background Standardized methods are needed to evaluate what occurs within the ‘black box’ of behavioral interventions to prevent pediatric obesity. The purpose of this research is to evaluate methods to specify the behavior change techniques used and the amount of time spent discussing target weight-related behaviors in an intervention for parents of children at risk for becoming overweight or obese. Methods Independent coders were trained to identify behavior change techniques and time spent discussing weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Because the FCU4Health is individually tailored to the needs of each child and family, we further specify whether a given technique is universal (received by all families in the program) or applied selectively based on needs identified in the family health behaviors assessment. We present the 23 techniques Jaka et al ( 27 ) found to be reported at least once in their evaluation of intervention protocols, manuscripts, and workbooks, indicating salience for childhood obesity programs whereas the remaining 70 techniques are unlikely to be relevant. Further, given that FCU4Health is a family-based intervention, certain behavior change techniques are taught to caregivers to then use with the child.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Because the FCU4Health is individually tailored to the needs of each child and family, we further specify whether a given technique is universal (received by all families in the program) or applied selectively based on needs identified in the family health behaviors assessment. We present the 23 techniques Jaka et al ( 27 ) found to be reported at least once in their evaluation of intervention protocols, manuscripts, and workbooks, indicating salience for childhood obesity programs whereas the remaining 70 techniques are unlikely to be relevant. Further, given that FCU4Health is a family-based intervention, certain behavior change techniques are taught to caregivers to then use with the child.…”
Section: Resultsmentioning
confidence: 98%
“…There is also a description of the activities (listed in the Method section) that were used in making the described adaptations. Finally, we use the JaKa et al ( 27 ) taxonomy to specify the behavior change techniques used in FCU4Health as a means of providing a standardized comparison to similar programs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations